Firm-level, macroeconomic, and institutional determinants of firm growth - Burger, Anže (Economic and business review, 2024)
To examine the main drivers of firm growth, we estimated a model integrating firm-level, industry-specific as well as country-level determinants, aiming at a comprehensive explanation of firm growth. We used a large dataset of European firms for the 2005–2017 period and combined Amadeus firm-level data with macroeconomic variables and multidimensional measures of institutional framework, based on a range of sources. Using different panel regression model specifications, we found the most consistent relationships for firm-level determinants. Among country-level determinants, infrastructure quality, inward FDI, natural resources, and inequality show a consistently positive and significant relation with firm growth.
Keywords: enterprises; growing company; management; podjetje; rastoče podjetje